1992
DOI: 10.1177/104225879201700108
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Entrepreneurial Socialization and Organization Formation

Abstract: This model applies theories of organizational socialization to characterize the aspiring entrepreneur's journey from neophyte to firm founder and to Identify factors that may Influence the transition from a pre-organization to the formation of a new organization. The model distinguishes two identifiable stages which shape organization formation—Anticipatory Socialization and New Entrepreneur Socialization. Anticipatory Socialization characterizes the predisposing characteristics and experiences that precede th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 15 publications
0
50
0
5
Order By: Relevance
“…In our introductory, theoretical discussion we have highlighted that both a negative and a positive association of entrepreneurship with benevolence can be established; based on person-organization fit theory (e.g., Schneider, 1987;Zhao et al 2010), on the entrepreneurs' socialization and roles literature (Starr & Fondas, 1992), and on fairness perceptions with respect to compensation schemes (Fehr & Schmidt, 2000;Lazear & Shaw, 2007). It requires empirical studies to inform research for the further development of such models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our introductory, theoretical discussion we have highlighted that both a negative and a positive association of entrepreneurship with benevolence can be established; based on person-organization fit theory (e.g., Schneider, 1987;Zhao et al 2010), on the entrepreneurs' socialization and roles literature (Starr & Fondas, 1992), and on fairness perceptions with respect to compensation schemes (Fehr & Schmidt, 2000;Lazear & Shaw, 2007). It requires empirical studies to inform research for the further development of such models.…”
Section: Discussionmentioning
confidence: 99%
“…Such arguments can be used to motivate a positive but also a negative association between benevolence and entrepreneurship. If entrepreneurship is associated with, and if entrepreneurs' role images corroborate, private profit maximization, then it is very likely that such people also allocate into entrepreneurship (see Starr & Fondas, 1992, on entrepreneurs' roles and socialization). The opposite can, however, be argued, too.…”
Section: Related Researchmentioning
confidence: 99%
“…This broad conception of an individual's career stands in contrast to most past studies in the entrepreneurship domain which have more narrowly focused on the decision to start a venture and become an entrepreneur (see e.g. Bird 1989; Lee and Wong 2004;Starr and Fondas 1992). Although we recognize the merit of previous studies in advancing our understanding of entrepreneurial career entry, we believe our broader conception of careers to be relevant in this case as we aim to understand how enterprising individuals prefer to progress in their entrepreneurial careers.…”
Section: Entrepreneurial Decision-makingmentioning
confidence: 90%
“…At the same time, both scholars and practitioners appear to assume that much of these differences must arise from various processes of socialization that might explain, even predict, the base rate characteristics of aspiring entrepreneurs (Starr and Fondas 1992). Indeed, Mitchell et al (2002) demonstrated that cultural differences explain some of the variance in venture-creation decisions among countries.…”
Section: Entrepreneurial Self-efficacy Contextualizedmentioning
confidence: 96%